Islamic Bank Financial Accountability in the Perspective of Shariah Enterprise Theory - Masiyah Kholmi (Yayasan Rumah Peneleh, 2023)
This study aims to examine financial accountability in the perspective of sharia enterprise theory at Bank Muamalat Indonesia. This is a qualitative research with a literature review on the annual financial reports of Bank Muamalat Indonesia for 2021. The study shows that Bank Muamalat Indonesia has carried out financial accountability in accordance with the principles of shariah enterprise theory which consists of three dimensions. First, there is vertical accountability to God physically and mentally in the form of distributing zakat and implementing programs to increase spirituality and religiosity. Second, there is horizontal accountability to humans, in the form of fulfilling material and spiritual needs. Third, there is horizontal accountability to nature or the environment and society in the form of corporate social responsibility programs. The novelty of the research is that financial accountability based on sharia enterprise theory is a new concept in Bank Muamalat Indonesia.